2015
DOI: 10.1248/yakushi.15-00109
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Pharmacists' Comprehensive Assessment of Medication Profiles in Dementia Patients

Abstract: In Japan the prevalence of dementia has increased considerably, and pharmacists are involved in addressing these patients' medication-related problems. Here, we determined whether pharmacists' comprehensive assessment of medication proˆles could reduce the burden of dementia patients' medication-related problems. In this historical cohort study 120 community pharmacies were randomly selected, and participating pharmacists completed questionnaires concerning comprehensive assessment of patient medication proˆle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…A multidisciplinary approach in educating patients and their caregivers about the importance of treatment and medication use is crucial, and the involvement of pharmacists should be considered, as it has been shown to improve compliance to medications. (41)…”
Section: Discussionmentioning
confidence: 99%
“…A multidisciplinary approach in educating patients and their caregivers about the importance of treatment and medication use is crucial, and the involvement of pharmacists should be considered, as it has been shown to improve compliance to medications. (41)…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining continuous pharmacological treatment of patients with Alzheimer’s disease can be difficult because of low persistence of treatment with AChEIs due to perceived medication inefficacy, unrealistic treatment expectations, and/or GI AEs [ 23 , 24 , 25 , 26 ]. Medication education and pharmacist-counseling have been associated with improved adherence and treatment persistence with AChEIs [ 27 , 28 , 29 ]. Inappropriate medications among community-dwelling persons with AD are relatively common including over-the-counter first-generation antihistamines with central anticholinergic AEs that can negatively impact cognition [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Community pharmacists play a role in dispensing AChEIs but also providing medication-related information, especially important for those with filling a medication for the first time. Inadequate pharmacist knowledge regarding donepezil GI AEs can potentially result in patient distress or early discontinuation [ 27 , 29 ], or to lack of understanding on how to potentially decrease AEs (e.g., taking medication with food, dividing daily dose and taking separately). Patients or caregivers should be informed that these AEs are usually transient and improve with continuous medication use [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that community pharmacists can optimize pharmacotherapy for BPSD by sharing patient information with their general practitioners [ 25 ]. A prospective cohort study previously conducted by the authors suggests that enhancing the collection of patient information by community pharmacists may help to reduce the burden of caregiving [ 26 ]. In addition, assessing the effectiveness of community pharmacists by monitoring caregiver burden has been initiated [ 27 ].…”
Section: Introductionmentioning
confidence: 99%